Long-Term Outcomes with ProlongedRelease Tacrolimus in Kidney Transplantation: A Retrospective Real-World Data Analysis - Gwinner, Wilfried; Anaokar, Swapneel; Blogg, Martin; Hermann, Birgit; Repetur, Carola Del Pilar; Schiffer, Mario (Annals of Transplantation, 2024)
Background: Long-term real-world outcomes data for kidney transplant recipients (KTRs) converting from immediate-release tacrolimus (IRT) to prolonged-release tacrolimus (PRT) are limited. Material/Methods: A retrospective, non-interventional review of adult KTRs treated with PRT for ≥1 month was conducted in Germany. Data were extracted from time of transplant (2008-2014) to 2018. Primary composite endpoints (graft loss, biopsy-confirmed acute rejection, graft dysfunction) and secondary endpoints (all-cause mortality, kidney function course, and tacrolimus dose/trough levels) were analyzed for sub-cohorts: de novo PRT, early conversion from IRT (within 6 months post-transplant), and late conversion (7 months to 3 years). Results: Analysis included 163 patients (101 de novo, 12 early converters, and 50 late converters). The overall Kaplan-Meier estimate of freedom from efficacy failure through 5 years was 0.537, (95% confidence interval (CI) 0.455-0.612) (de novo: 0.512 [0.407-0.608]; early converters: 0.500 [0.208-0.736]; late converters: 0.594 [0.443-0.717]). The overall survival rate was 0.925 (95% CI 0.872-0.957) (de novo: 0.900 [0.823-0.945]; early converters: 0.917 [0.539-0.988]; late converters: 0.977 [0.846-0.997]). During follow-up, there was a gradual reduction in tacrolimus dose and trough levels; kidney function remained stable in all cohorts. Multivariable analysis found retransplantation, organ donor quality, best estimated glomerular filtration rate 8-12 weeks after transplant, and treatment center (between-center differences in age, sex, donor status/quality) were significantly associated with efficacy failure. Conclusions: There was no difference in long-term survival profiles between KTRs who received PRT de novo vs those who converted from IRT, with 5-year survival remaining high in both groups.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Clinical Study; Immunosuppression Therapy; Kidney Transplantation; Retrospective Studies; Tacrolimus